Talent development and expertise in sport - Phillips, E.; Davids, K.; Araujo, D.; Renshaw, I. (Complex systems in Sport, 2014)
Complex systems theory is an appropriate functional framework for expert performance research because it can address questions that other frameworks do not have the language and tools to pose. This chapter has discussed several concepts with important implications for expertise and talent development researchers, including the concepts of self-organization under constraints; emergence; metastability, creativity; and degeneracy, stabilities and instabilities over different timescales. These ideas on the dynamic interactions between genes and environment and the functional role of degeneracy in the human nervous system require a multidisciplinary theoretical perspective to explain the acquisition of expertise in sport. Within this overarching theoretical framework, it has been argued that the same performance outcomes can be achieved in diverse ways as individual performers attempt to satisfy the unique constraints on them (Davids et al. 2003). Genetic diversity may be responsible for a small part of training or performance response differences between individuals and only when there is a favourable interaction with important environmental constraints are performance benefits observed. Phenotypic expression of behaviour might be best understood at the level of individual interactions with key environmental and task constraints. This is particularly relevant for researchers considering effects of time spent in deliberate practice in sport since there is often !ittle mention of genetic constraints on the acquisition of expertise. Given differences in genetic contributions, performance variations are more likely to assert themselves under intensive practice regimens. The acquisition of expertise is domain specific and is about adaptation to the environment through satisfying unique constraints which impinge on each developing expert. Expertise acquisition emphasizes the changing nature of the performcr-environment relationship through development and gaining experience through training, practice, coaching and competing. A comprehensive examination of expertise involves identifying the intrinsic dynamics of each individual and the specific rate limiters and constraints which shape their behaviour. Each individual athlete comes to a performance context with a particular set of intrinsic dynamics that has al ready been shaped by genes, development and early experiences. Individualized pathways to expert performance are expected because of the uniqueness of these dynamics constraints.